Combined use of gas chromatography and HPLC-ESI-Q-TOF to assess the culinary uses of archaeological Santa María style ceramic vessels from El Colorado (Catamarca, Argentina) - Lantos, Irene Johanna (2020)
In this paper, an interdisciplinary investigation was carried out to study if Santa Maria tricolor style vessels were used as culinary equipment in a 14th century ad domestic cooking space in El Colorado (Yocavil valley, Catamarca, Northwest Argentina) and to question the long-established idea that Santa Maria vessels were exclusively funerary objects. The combined use of gas chromatography (GC-FID), gas chromatography–mass spectrometry (GC-MS), and high-performance liquid chromatography coupled to electrospray ionization and quadrupole time-of-flight mass spectrometry (HPLC-ESI-Q-TOF) to study residual lipids from Santa Maria style vessels provided valuable information on their ancient use. Also, an ordinary striated style ceramic pot with distinct visible soot marks, as well as sediments from the cooking area, was studied for comparative purposes. Fatty acid, sterol, and acylglyceride profiles were characterized, and markers of food sources were searched in the complex mixtures. We identified intact triacylglycerides (TAGs) in the archaeological samples, even unsaturated, indicating exceptional preservation of lipids in the ceramic matrixes. Cholesterol or cholesterol oxidation products were observed in all ceramic containers, as well as plant sterols (stigmasterol, sitosterol) in two containers. Markers for ruminant lipids, such as TAGs that contain odd-chain fatty acids, were found, supported by the identification of odd-chain and branched-chain fatty acids with GC-FID and GC-MS. This evidence contributes to the hypothesis that Santa Maria vessels were used for culinary purposes in this archaeological domestic cooking space.